2017
DOI: 10.17060/ijodaep.2014.n1.v7.800
|View full text |Cite
|
Sign up to set email alerts
|

Bullying E Suas Dimensões Psicológicas Em Adolescentes

Abstract: Understanding the psychological mechanisms acting in shares of specific violence, such as bullying, constitutes an important step in the educational interventions that promote moral education objectified by educational institutions. In this sense, the current research aimed to relate bullying to representations of self and the ways in which the subject is self-regulating to choose justifications for their commitments or moral disengagements in situations where bullying is present. The results indicate that sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…Those involved in the dynamics of maltreatment as potential aggressors have one point in common: they lack moral sensitivity; being exactly those who are most morally disengaged (Tognetta et al, 2014), justifying their conducts from the minimization of the impacts of violence and the valorization of self over the other.…”
Section: Bullying Its Characters and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those involved in the dynamics of maltreatment as potential aggressors have one point in common: they lack moral sensitivity; being exactly those who are most morally disengaged (Tognetta et al, 2014), justifying their conducts from the minimization of the impacts of violence and the valorization of self over the other.…”
Section: Bullying Its Characters and Characteristicsmentioning
confidence: 99%
“…A study that sought to measure the participation and the relationship between aggressors, victims and bystanders in public and private schools in Brazil found that, among all those involved in bullying situations, 15.9% called themselves victims, 19.5% said they had participated in perpetuating the aggressions as perpetrators, and another 62.8% reported being bystanders, just watching the scenes of abuse and mistreatment (Tognetta et al, 2014).…”
Section: Bystanders: Those Who Witness the Violencementioning
confidence: 99%
“…Pesquisas têm evidenciado que o bullying também está relacionado à busca do autor por status social, poder e pertencimento no grupo (DEL BARRIO et al, 2005;JUNOVEN;GALVAN, 2008;ROLAND, 2010;SALMIVALLI, 2010;PEETS, 2010), além de ser um problema moral, visto que valores como respeito, justiça e igualdade estão ausentes nestas ações (MENESINI et al, 2003;MENESINI, 2002;TOGNETTA, 2011;TOGNETTA;AVILÉS MARTINEZ;ROSÁRIO, 2014).…”
Section: Introductionunclassified
“…A construção de valores morais é, portanto, condição sini-qua-non quando se deseja formar pessoas que se respeitem.Certamente, existe uma intrínseca relação entre a ocorrência do bullying e o reforçamento que recebem aqueles que agem mal pelos risos e aprovações de sua plateia. Se são aprovados como admiráveis os mais "poderosos", os mais "inteligentes", os "mais ricos", ou quaisquer que sejam as diferenças, aqueles que atuam como agressores se constituirão fortalecidos por quem assiste(MENIN, 2002;TOGNETTA;AVILÉS MARTINEZ;ROSÁRIO, 2014;VAN…”
unclassified